RITUAL DAMAR SEWU DALAM UPACARA SEREN TAUN SEBAGAI SUMBER BELAJAR MATA PELAJARAN SOSIOLOGI - Khairani, Salsabila; Wildan, Dadan; Komariah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study discusses the importance of preserving and understanding local cultural heritage in facing globalization challenges that threaten the sustainability of local cultures. The Damar Sewu ritual as a learning resource in sociology education focuses on cultural values, symbolism, and its potential in developing the Indonesian education curriculum. The research method used is a qualitative approach with descriptive analysis through literature review. The results show that the Damar Sewu ritual contains various symbols and profound meanings that reflect social values, norms, and belief systems of the local community. In sociology education, the discovery learning method can be applied to provide direct experiences to students about the values embedded in the Damar Sewu ritual. Through this learning process, students not only understand sociological theories abstractly but also experience how these values are applied in the daily lives of the local community, strengthening students' understanding of the importance of preserving and appreciating cultural heritage in building an inclusive and diverse national identity.